Quantum dots enhanced stability of in-situ fabricated perovskite nanocrystals based light-emitting diodes: Electrical field distribution effects - Xue, Xulan; Li, Menglin; Liu, Zhenjie; Wang, Chenhui; Xu, Jincheng; Wang, Shuangpeng; Zhang, Hanzhuang; Zhong, Haizheng; Ji, Wenyu (Fundamental research (Beijing), 2025)
•Quantum dot (QD) enhanced stability of perovskite light-emitting diodes (PeLEDs) was achieved by introducing preformed CdSe/ZnS core-shell QDs in anti-solvent during in-situ ligand assisted reprecipitation fabrication of FAPbBr3 perovskite nanocrystals (PNCs) films.•The T50 lifetime under the initial luminance of 1021 cd/m2 approaches 83 minutes for a typical PeLED.•The enhanced stability can be mainly attributed to the electric field redistribution suppressed ion migration due to the presence of QD monolayer between the PNC film and electron transport layer in the device. With the development in fabricating efficient perovskite light emitting diodes (PeLEDs), improving the operating stability becomes an urgent task. Here we report quantum dot (QD) enhanced stability of PeLEDs by introducing CdSe/ZnS core-shell QDs in toluene anti-solvent during in-situ fabrication of FAPbBr3 perovskite nanocrystals (PNCs) films. In comparison with PNC films with pristine toluene as the anti-solvent, the as-prepared FAPbBr3 PNC films with a QD monolayer on the surface exhibit improved photoluminescence quantum yield, enhanced photostability and better reproducibility. Benefiting from these advantages, the peak luminance and the maximum external quantum efficiency of the PeLED containing QD monolayer are increased from 6807 cd/m2 to 86,670 cd/m2 and 2.4% to 7.1%, respectively. The T50 lifetime under the initial luminance of 1021 cd/m2 approaches 83 minutes. Based on electrical field simulation and transient electroluminescence measurements, the enhanced stability can be mainly attributed to the electrical field redistribution induced by the QD monolayer. This work demonstrates that the combination of QDs and perovskites provides an effective strategy to address the operational stability of PeLEDs. The insights into electrical field distribution effect will make great impact on stability improvement of other perovskite based devices. [Display omitted]